1981
DOI: 10.1177/002383098102400201
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Characteristics of Female Voices

Abstract: This study attempted to define perceptually salient characteristics in the voices of 30 young adult females, as perceived by female and male listeners. The listeners were asked to rate the voices on 20 individual seven point semantic differential scales representing unique vocal features. The ratings were subjected to factor analysis involving both orthogonal and oblique rotation of the data. Both groups of listeners identified two similar factors, one of which appeared to describe "passive", traditionally fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Even though pitch did not negatively correlate with attractiveness ratings, it is possible that the low pitch contributed to a prosodic pattern that independently drove the attractiveness ratings. For example, even though women lower their average f 0 and make their speech breathy when asked to simulate sexiness (Tuomi & Fischer, 1979), perception of sexiness is not always associated with the perception of lowered pitch or breathiness alone (Batstone & Tuomi, 1981). This suggests that the pitch change may only be a part of a constellation of acoustic factors that is perceived holistically.…”
Section: Discussionmentioning
confidence: 99%
“…Even though pitch did not negatively correlate with attractiveness ratings, it is possible that the low pitch contributed to a prosodic pattern that independently drove the attractiveness ratings. For example, even though women lower their average f 0 and make their speech breathy when asked to simulate sexiness (Tuomi & Fischer, 1979), perception of sexiness is not always associated with the perception of lowered pitch or breathiness alone (Batstone & Tuomi, 1981). This suggests that the pitch change may only be a part of a constellation of acoustic factors that is perceived holistically.…”
Section: Discussionmentioning
confidence: 99%
“…During the recording session the participants read several passages, one of which was the "Rainbow Passage" (Fairbanks, 1940, p. 127), which is the only passage that was used as stimuli in the research reported in this article. This passage is commonly used in voice research for a number of reasons, the most relevant for our purpose being its unvalenced content and neutrality with regard to gender stereotypes (e.g., Addington, 1968;Batstone & Tuomi, 1981;Ray, 1986). From these recordings, 47 female voices and 47 male voices saying the first two sentences of the "Rainbow Passage" were used as the final stimuli.…”
Section: Methods Recording Participants and Proceduresmentioning
confidence: 99%
“…On the other hand, female English speakers often sound harsh, raucous, rude, or overly masculine to a Japanese ear. Batstone and Tuomi's (1981) study of perception of female voice quality showed that men found "passive" characteristics-soft, gentle, sweet-most salient, whereas women found "active" oneslively, colorful, interesting-most salient. This suggests an interesting difference between male and female perceptions of female characteristics and roles.…”
Section: Paraverbal Featuresmentioning
confidence: 99%